Clinical features and corneal optical anisotropies in a rabbit model of limbal stem cell deficiency - Kobashigawa,Karina Kamachi (2018)
ABSTRACT Purposes: To investigate the intra-laboratory reproducibility of clinical features and to evaluate corneal optical anisotropies in a rabbit model of limbal stem cell deficiency. Methods: Limbal injury was induced in the right eye of 23 adult New Zealand White rabbits using a highly aggressive protocol that combined 360 degrees limbal peritomy, keratolimbectomy, alkaline chemical burn, and mechanical removal of the epithelium. Clinical evaluation of the injured eyes was performed for 28 days and included corneal impression cytology. Corneas with a severe clinical outcome set typical of limbal stem cell deficiency were then collected, subjected to a histopathological examination, and examined for optical anisotropies. Corneas from healthy rabbit eyes were used as controls. Differences in optical path due to stromal collagen birefringence, as well as linear dichroism related to the expression and spatial orientation of glycosaminoglycan chains from proteoglycans, were measured from cross-sections under a quantitative polarized light microscope. Results: One eye showed signs of hypopyon and was excluded. Signs of ocular inflammation were observed in all eyes studied (n=22). Corneal impression cytology did not detect goblet cells. Twelve of the 22 corneas presented a clinical outcome set typical of limbal stem cell deficiency, which is characterized by the presence of epithelial defects, inflammatory cells, moderate-to-severe opacity, and neovascularization. Microscopic studies under polarized light revealed that relative to controls, limbal stem cell deficiency caused a 24.4% increase in corneal optical path differences. Further, corneas with limbal stem cell deficiency were less dichroic than controls. Conclusions: These results suggest that rabbit models of limbal stem cell deficiency must be rigorously screened for use in preclinical studies to ensure experimental homogeneity because protocols used to create limbal stem cell deficiency could be not associated with good intra-laboratory reproducibility of clinical features. Limbal stem cell deficiency, as induced herein, altered the optical anisotropic properties of the corneal stroma. Such alterations are indicative of changes in collagen packing and the spatial orientation of glycosaminoglycan chains from proteoglycans. Knowledge of these changes is important to potentiate strategies aimed at restoring the morphofunctional integrity of the corneal stroma affected by limbal stem cell deficiency.